2020
DOI: 10.1371/journal.pone.0231543
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperglycemic activity of myricetin, through inhibition of DPP-4 and enhanced GLP-1 levels, is attenuated by co-ingestion with lectin-rich protein

Abstract: Dipeptidyl peptidase-4 (DPP-4) is a proteolytic enzyme responsible for the rapid degradation of Glucagon-like peptide 1 (GLP-1) that is required for the secretion of insulin. DPP-4 also influences activation of node like receptor family, pyrin domain containing 3 (NLRP3) inflammasome under diabetic conditions. Although several polyphenols are reported for various bioactivities, they are consumed as part of the food matrix and not in isolation. Horsegram (Macrotyloma uniflorum) is a rich source of myricetin (My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Verdc.) seed coat, decreased in the liver of streptozotocin-induced diabetic male Wistar rats, the gene expression of NLRP3, ASC and caspase-1, leading to a reduction in blood glucose levels and in liver dipeptidyl peptidase-4 and antioxidant enzyme activities, as well as leading to an improvement in plasma insulin levels [ 101 ]. Furthermore, other plant phenolic compounds exert similar effects: freeze-dried red raspberry powder enriched in polyphenols ameliorated levels of blood glucose, insulin resistance and glucose intolerance and the accumulation of hepatic lipids.…”
Section: Nutraceutical Compounds the Nlrp3 Inflammasome And Type mentioning
confidence: 99%
“…Verdc.) seed coat, decreased in the liver of streptozotocin-induced diabetic male Wistar rats, the gene expression of NLRP3, ASC and caspase-1, leading to a reduction in blood glucose levels and in liver dipeptidyl peptidase-4 and antioxidant enzyme activities, as well as leading to an improvement in plasma insulin levels [ 101 ]. Furthermore, other plant phenolic compounds exert similar effects: freeze-dried red raspberry powder enriched in polyphenols ameliorated levels of blood glucose, insulin resistance and glucose intolerance and the accumulation of hepatic lipids.…”
Section: Nutraceutical Compounds the Nlrp3 Inflammasome And Type mentioning
confidence: 99%
“…Recently, sitagliptin was reported to increased muscle mass and muscle/fat ratio in T2DM [ 67 ], and natural DPP-4 inhibitors such as chrysin and galangin were reported to promote SM cell proliferation [ 68 , 69 ]. Furthermore, in a diabetic animal model, myricetin administration reduced DDP-4 expression in muscle [ 70 ]. Overall, these studies revealed that DPP-4 inhibitors have a positive effect on SM, increasing SM cell proliferation and the muscle/fat ratio in diabetic patients.…”
Section: Dpp-4 Inhibition and Skeletal Muscle Functionmentioning
confidence: 99%
“…Macrotyloma uniflorum (horsegram) is a legume grown mainly in dry regions of Australia, Burma, India, and Sri Lanka and contains high concentrations of myricetin, which has been shown to have anti-hyperglycemic properties. Myricetin also inhibited DPP-4 (IC 50 of 4.8 μM), and thus, increased serum GLP-1 and insulin levels and ameliorated the manifestations of T2DM [ 70 ].…”
Section: Natural Phytochemicalsmentioning
confidence: 99%
“…In animal studies, GLP-1 secretion can be induced by acute (single) administration of curcumin [ 116 ], as well as the ginsenoside metabolite Rg3 [ 111 ]. Increment of plasma GLP-1 levels following chronic administration (oral or intraperitoneal) of apigenin [ 115 ], genistein combined with metformin [ 117 ], hispidulin [ 112 ], isoquercitrin [ 113 ], luteolin [ 118 ], myricetin [ 119 ], grape seed proanthocyanidins [ 120 ], procyanidin [ 121 ], and resveratrol [ 122 ] have been reported.…”
Section: Phytochemicals and Glp-1mentioning
confidence: 99%
“…Some compounds (isoquercitrin and myricetin) reportedly possess inhibitory activity against the DPP-4 enzyme, which is considered to contribute to the promotive effect on GLP-1 levels [ 113 , 119 ]. Flavonoids mediate various protective effects against obesity, diabetes, and other metabolic diseases by targeting various organs, tissues, and cells, as described previously.…”
Section: Phytochemicals and Glp-1mentioning
confidence: 99%